DEv-PROMELA: an extension of PROMELA for the modelling, simulation and verification of discrete-event systems. (2017) - Yacoub, Aznam; Hamri, Maamar El Amine; Frydman, Claudia; Seo, Chungman; Zeigler, Bernard P.
PROMELA is a well-known formalism for the modelling and the verification of concurrent systems. PROMELA deals with high-level specifications. As a result, PROMELA models are expressed in a high-level abstraction which does not consider explicit representation of time or events for example. But, the efficiency of the processes of verification and validation relies on the accuracy of the models. That is why we propose, in this paper, work to develop a new extension of PROMELA for the modelling of discrete-event systems. The verification of these models is then done by combining formal verification and simulation-based verification using SPIN and the tool DEv-PROMELA Studio, or using any existing DEVS simulators.